DEVELOPMENT OF A CARTESIAN COORDINATE MODULE TO IMPROVE THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS - Laia, Marius Ferdi (Universitas Nias Raya, 2023)
Mathematics is very important in everyday life, because human mathematics can think logically and argue. Many students think that mathematics is learning that is not fun and results in students being less able to understand mathematical concepts so that the level of student learning decreases, plus the source material presented is lacking. So that researchers conduct research on module development that can support students in learning mathematics and improve students' abilities in understanding concepts. This study aims to develop a module that refers to increasing the ability to understand mathematical concepts, with the material presented is Cartesian coordinate material. The module development procedure in this study is the 4-D development model. Data collection techniques used are student learning outcomes tests and questionnaires. The instruments used were validation sheets, student response questionnaires and pretest-posttest validation sheets. Based on the validity test, the results of the research show that the Cartesian coordinate module is very valid with a validity level of 86.4%. The results of the practicality test in the limited trial with a total of 16 students obtained a very practical Cartesian coordinate module with a percentage of 90.3%, and a field trial with a total of 22 students obtained a very practical Cartesian coordinate module with a practicality level percentage of 85.2%. . The module has met the effectiveness criteria based on the results of limited trials with the acquisition of a learning completeness score of 0.60 in the medium category, the results of field trials with the acquisition of a learning completeness score of 0.73 in the high category. This shows that the developed module is valid, practical and effective. The researcher hopes that this module can be used in learning, especially Cartesian coordinate material to improve students' conceptual understanding abilities.